Development of a Multi-Domain RFID Security Model for Global Supply Chains, and a Practical Framework for Model Adoption - Lam, Philip Yuk-Fai (Curtin University, 2020)
Radio Frequency Identification (RFID) has been identified as a practical technology to transform supply chain management and drive supply chain innovations, yet at the same time its usage can cause security vulnerability issues. As the use of RFIDs grows, security vulnerability issues also grow in scope and scale. This research is to develop an RFID security model and a practical framework that can be used to help develop better end-to-end security practices.